Reestruturação do layout produtivo em uma empresa do ramo alimentício com a utilização do Lean Board Game - Camargo, Felipe Haeflinger (2023)
It is a fact that a layout restructuring and an analysis of the business production sector can bring many positive points to a company that wants to remain firm in the market, always seeking the best quality for its product aimed at the end customer. In this sense, this study aims to restructure the production layout of a food company using the Lean Board Game. The literature review deals with the topics of Layout, Lean Production, Continuous Flow, Physical Arrangement, Production Bottlenecks, Lean Board Game and Pull Process. The study presents as a methodological procedure the collection of data from the production sector in a company in the food sector, with the objective of identifying bottlenecks and presenting a layout restructuring based on the application of the Lean Board Game. The data was obtained through a questionnaire applied to employees in the production sector, after which the sector was restructured to a new production layout, presenting the positive points and improvements. The main results obtained present a better meeting of production demand and improvement in the production flow.